2021
DOI: 10.1002/hyp.14088
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic properties affected by litter and stem cover under overland flow

Abstract: Vegetation stems and litter cover have different effects on sediment transport capacity under the same experimental conditions, which in essence, may be due to differences in their hydraulic properties, but the availability of comparative studies is limited. This study aimed to compare the hydraulic properties affected by litter and stem cover, compare differences in the drag forces exerted by litter and stems on overland flow, and develop new Manning's n and flow velocity equations for litter cover. Two serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Ding and Li (2016) also found that there was little difference in Re on slopes with different grass cover, and identified that Re increased with the rise of discharge. Ding et al (2021) reached a similar conclusion. found no obvious trend between Re and the amount of litter after having conducted experimental tests simulating rainfall on a slope covered by litter.…”
supporting
confidence: 61%
“…Ding and Li (2016) also found that there was little difference in Re on slopes with different grass cover, and identified that Re increased with the rise of discharge. Ding et al (2021) reached a similar conclusion. found no obvious trend between Re and the amount of litter after having conducted experimental tests simulating rainfall on a slope covered by litter.…”
supporting
confidence: 61%
“…A newer formulation describing depth-dependent roughness based on the Manning equation has been provided by Fu et al (2019). Later the equation has been adapted to be valid for litter cover (Ding et al, 2021). Fu conducted several laboratory experiments for a vegetation cover from 0 to 30% with artificial plants with a height of 12 cm.…”
Section: Fu's Equationmentioning
confidence: 99%